Teachers' meetings as perceived by public elementary school teachers of Zamboanga City - Nazario, Avelina D. (s.n.], 1971)
This study was designed to determine how teachers perceive teachers' meetings in Zamboanga City Division. Data were obtained through checklists and rating scale answered by 500 elementary school teachers, and through memoranda and circulars, records of teachers' meetings from 1968-1969, and interviews. It was concluded that elementary school teachers of Zamboanga City perceive meetings as favorable if its agenda is planned cooperatively by the principal and staff; if copies of the agenda are available to the staff at least two days before the meeting; if the meetings are scheduled and held regularly, once a month and during afternoons with a comfortable atmosphere; and if there is a panel discussion afterwards.